2014
DOI: 10.1007/s00394-013-0641-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic inflammation induced by high-fructose diet is associated with altered 11βHSD1 expression in the liver of Wistar rats

Abstract: High-fructose diet does not influence hepatic glucocorticoid signaling downstream of the receptor, permitting development of NFκB-driven inflammation. The alteration in 11βHSD1 expression is most likely the consequence of enhanced inflammation, finally leading to disruption of insulin signaling in the rat liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 51 publications
5
30
0
1
Order By: Relevance
“…Since the increase in SOD2 activity in fructose‐fed rats was not accompanied by increased expression or enhanced activity of other antioxidant enzymes or damage of cellular macromolecules, we can assume that the expected rise in concentration of hydrogen peroxide represents a transient and regulated stage during the adaptation to nutritional excess. Using the same animal model, we have previously observed that high‐fructose diet impairs hepatic insulin sensitivity; therefore the absence of oxidative stress observed herein suggests that the rise in hydrogen peroxide concentration in the liver of fructose‐fed rats might represent a cellular response aimed to restore hepatic insulin sensitivity at the early stage of the disease. However, the possibility that prolonged fructose overconsumption might finally lead to oxidative stress, and consequently contribute to progression and aggravation of metabolic disturbances in later adulthood, should also be investigated.…”
Section: Discussionsupporting
confidence: 55%
“…Since the increase in SOD2 activity in fructose‐fed rats was not accompanied by increased expression or enhanced activity of other antioxidant enzymes or damage of cellular macromolecules, we can assume that the expected rise in concentration of hydrogen peroxide represents a transient and regulated stage during the adaptation to nutritional excess. Using the same animal model, we have previously observed that high‐fructose diet impairs hepatic insulin sensitivity; therefore the absence of oxidative stress observed herein suggests that the rise in hydrogen peroxide concentration in the liver of fructose‐fed rats might represent a cellular response aimed to restore hepatic insulin sensitivity at the early stage of the disease. However, the possibility that prolonged fructose overconsumption might finally lead to oxidative stress, and consequently contribute to progression and aggravation of metabolic disturbances in later adulthood, should also be investigated.…”
Section: Discussionsupporting
confidence: 55%
“…Daily fructose consumption from food or drinking water has been demonstrated to stimulate de novo lipogenesis and results in chronic low-grade inflammation and insulin resistance. 38, 39 Previous studies have suggested that NAFLD may be associated with an increased formation of reactive oxygen species in the liver and an induction of TNFα. 40 Recent study showed that lipid peroxidation results in the formation of HNE and upregulates various signaling intermediates that regulate cellular activity and dysfunction via a process called redox signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, high fructose consumption in rats results in hepatic increase of TNFα mRNA expression via NFκβ-dependent transcriptional upregulation 112 . TNFα induces serine phosphorylation of IRS-1 through inhibition of serine phosphatases (such as protein phosphatase 2A or PP2A) or activation of serine kinases (such as JNK or protein kinase C theta) leading to disruption of insulin signaling in the liver 113 .…”
Section: ) Harmful Effects Of Hepatotoxic Carbohydratesmentioning
confidence: 99%